Progress, Advantages, and Challenges of Topological Material Catalysts. Issue 4 (3rd February 2022) - Xie, Ruikuan; Zhang, Tan; Weng, Hongming; Chai, Guo-Liang
Abstract : Topological materials is one of the hottest topics in condensed matter physics because of its exotic properties such as robust metallic boundary states, Fermi arcs, and the spin‐momentum‐locking helicity. The topologically protected conducting boundary states spanning the whole bandgap are expected to serve as robust and wide‐range‐energy transition states facilitating catalytic reactions. Recently, some topological materials have been found to be high‐performance catalysts, which might open an emerging research field. Herein, an overview of topological materials is given and then recent progress in topological material catalysts (TMCs) is presented. As it is a new field, more detailed and accurate mechanisms behind the high performance of TMCs are urgently needed. Combining theoretical and experimental studies is a promising way to resolve these puzzles. Heterostructures, dopants, and defects have the chance to tune the catalytic activity of TMCs while retaining topological surface states (TSSs). Also, more TMCs are needed to be discovered, and more catalytic reactions are to be investigated for TMCs in the future. Abstract : Topological material catalyst (TMC) has shown exciting potential which might open an emerging research field. The progress, advantages, and challenges for TMC are presented in this Perspective. The main challenge is that the mechanism behind high performance is unclear. Topological surface state is supposed to be the key factor and possible methods to investigate it are put forward.